Fencing in the dark Japan, China, and the Senkakus - Sunohara, Tsuyoshi 1961-
Sino-Japanese relations were seriously rattled in September 2010 when a Chinese fishing boat rammed a Japanese Coast Guard patrol ship in Japanese waters off the Senkaku Islands. This was compounded in April 2012 when Tokyo Governor Ishihara Shintaro announced that he planned to buy the islands and added, 'if this means war with China, so be it.' Alarmed at the prospect of Ishihara owning the islands, Democratic Party of Japan prime minister Noda Yoshihiko moved to see if there was some way the government could buy them instead, even knowing this would be seen as nationalization. Top officials in foreign policy, defense, and other areas met at Kantei (officially the Prime Minister's Official Residence, but actually his offices) to find an out that would pre-empt Ishihara without provoking China (which also claimed the islands). This book tells the gripping story of what happened and why."--Dust jacket.